Anticonvulsant‐Related Psychoses in Epilepsy - Matsuura, Masato; Suzuki, Takeshi; Sakai, Teiichiro; Kojima, Takuya (Epilepsia (Copenhagen), 1998)
Purpose: The study aimed to clarify any association between the development of a first psychotic episode and anticonvulsive drug therapy (AEDs) for epilepsy and to propose possible interventions to prevent the development of such psychoses. Methods: The subjects were 44 (20 male and 24 female) consecutive patients attending our clinic, who had epilepsy and current or previous psychotic symptoms. The psychotic symptoms were defined as delusions, hallucinations, or other productive symptoms or a combination of these under clear consciousness. Results: Three of the subjects had idiopathic generalized epilepsy, one had symptomatic generalized epilepsy, 22 had temporal lobe epilepsy, and 18 had non‐temporal lobe epilepsy. At the time of the study, nine patients had been free of seizures for ≥3 years, six had experienced one or two seizures within the past 3 years, 12 had yearly seizures, and 17 had monthly seizures. Two groups could be distinguished: in 27 (61%) patients, the first psychotic episode was unrelated to changes in the AEDs, whereas in 17 (39%) patients, the development of psychoses showed a temporal relation with changes in the AED. The mean age (41.5 and 40.6 years), mean age at the onset of epilepsy (14.2 and 12.6 years), type of epilepsy, and seizure frequencies did not differ between the two groups. Although the number of AEDs prescribed at the time of onset of the first psychotic episode did not differ between the groups, phenytoin (PHT) or carbamazepine (CBZ) were most frequently used in the non‐drug‐related group, whereas zonisamide (ZNS) and phenobarbital (PB) were the most common treatments in the drug‐related group. Among the nonDrug‐related group, many of the patients developed psychoses with no temporal relation to changes in seizure frequency. Most of these were schizophrenia‐like psychoses with a chornic course. Among the drug‐related group, seven patients developed psychoses after starting an add‐on therapy with a new AED, many of which were alternative psychoses characterized by delusional psychosis with remission. Six patients developed psychoses after abruptly discontinuing their AEDs. These were mostly postictal psychoses characterized by polymorphic psychosis and relapses. Four patients developed psychoses after taking overdoses of PHT or polypharmacy, half of which were schizophrenia‐like psychoses with remission. Almost all patients in both groups were treated with psychotropic drugs during their psychotic episodes, but 59% of the nonDrug‐related and 6% of the drug‐related groups followed a chronic clinical course. Fifteen percent of the nonrelated group and 35% of the drug‐related group relapsed with psychoses between 6 months and 5 years after remission of their first episode, and many of these did not receive psychotropic drugs as maintenance therapy. The fact that relapses in the patients in the drug‐related group showed no association with changes in AEDs suggests that they may have been vulnerable to psychoses. Conclusions: Add‐on therapy with a potential new AED, as well as abrupt discontinuation or overdoses of existing AEDs, may increase the risk of developing psychoses. Changing drug regimens gradually and maintaining compliance are crucial factors in preventing psychoses in patients with epilepsy.